Using rock physics to determine uncertainties in pore-fluid and lithology-estimates from seismic attributes in the Bredasdorp Basin, offshore South Africa - Tönsing, Tobias R (Department of Geological Sciences, 2014)
This study is aimed at developing a workflow for quantitative seismic interpretation. The workflow generated probability maps of various facies and pore-fluid by combining seismic attributes and wireline log data through rock physics relationships and supervised statistical classification. The workflow was developed mainly for hydrocarbon exploration, but could be used for other purposes, provided the target is seismically detectible. Any prior regional geological knowledge is built into the workflow, by extending the training date appropriately. The workflow aims to maximize the extraction of quantitative geological parameters from data that are most commonly acquired for hydrocarbon exploration, namely seismic and wireline log data. The workflow is presented using 3D seismic data from the Bredasdorp Basin offshore South Africa's south-coast. Wireline log data from the E-BX1 borehole are also used in the study, as well as regional geological interpretations. The study focused on the siliciclastic Aptian "13B" sequence, which was encountered at a depth of 2500 m below sea level at borehole E-BX1. Two massive 13B sandstone units were encountered at E-BX1. The lower unit is 50 m, and the upper 20 m thick. Both are water wet. The results of this study suggest that there are two oil accumulations at the 13X level around E-BX1. This is indicated by the high probability predicted for oil-bearing sandstone in these two areas.